Design of worm gears with optimal geometric parameters based on minimization of loses in gearing - Tkach, Pavlo; Nosko, Pavlo; Boyko, Grygory; Bashta, Oleksandr; Bashta (Sheremet), Alla (My University, 2018)
The mathematical model of definition of losses in gearing worm gears and their de-crease on 10 … 15 % is stated at definition on the basis of planning mathematical experiment of rational parameters of transfers.
Keywords: mathematical model; worm gears; experiment; математична модель; черв'ячні передачі; експеримент; кафедра технології оздоровчих продуктів